Case Report: Hemoptysis secondary to fish bone migration into the lung parenchyma - Chen, Huan; Li, Qi; Guo, Xinyi; Huang, Meiyuan; Tan, Nianxi (Frontiers in Medicine, 2025)
Hemoptysis caused by transmural migration of ingested fish bones into lung parenchyma is exceptionally rare. A 71-years-old diabetic woman presented with 20-days recurrent hemoptysis, exacerbated in supine position. Three months prior, she experienced fish bone impaction with negative laryngoscopy. On re-presentation, contrast-enhanced CT revealed a foreign body embedded in the right upper lobe surrounded by an inflammatory pseudotumor. Thoracoscopic wedge resection confirmed a fish bone intraparenchymal migration with suppurative abscess. The patient recovered uneventfully and remained asymptomatic at 1-month follow-up. This case highlights that even with negative laryngoscopy, patients with fish bone ingestion history require prompt CT to prevent delayed complications. Thoracoscopic resection is effective for pulmonary migration with inflammatory encapsulation.